Abrupt fault remaining useful life estimation using measurements from a reciprocating compressor valve failure. (15th April 2019) - Loukopoulos, Panagiotis; Zolkiewski, George; Bennett, Ian; Sampath, Suresh; Pilidis, Pericles; Li, X.; Mba, David
Highlights: Comparison of prognostics methods on instantaneous failure mode. Benchmarking of prognostics methods on industrial reciprocating compressor. Use of actual, non-uniformly sampled valve failure measurements. Proposal SOM as prognostics tool, and RUL estimation variation based on SOM or KNNR. Proposal Hotelling T 2 and Q residuals metrics as health indicators and RUL predictors. Abstract: One of the major targets in industry is minimisation of downtime and cost, and maximisation of availability and safety, with maintenance considered a key aspect in achieving this objective. The concept of Condition Based Maintenance and Prognostics and Health Management (CBM/PHM), which is founded on the principles of diagnostics, and prognostics, is a step towards this direction as it offers a proactive means for scheduling maintenance. Reciprocating compressors are vital components in oil and gas industry, though their maintenance cost is known to be relatively high. Compressor valves are the weakest part, being the most frequent failing component, accounting for almost half maintenance cost. To date, there has been limited information on estimating Remaining Useful Life (RUL) of reciprocating compressor in the open literature. This paper compares the prognostic performance of several methods (multiple linear regression, polynomial regression, Self-Organising Map (SOM), K-Nearest Neighbours Regression (KNNR)), in relation to their accuracy and precision, using actual valve failure data captured from an operating industrial compressor. The SOM technique is employed for the first time as a standalone tool for RUL estimation. Furthermore, two variations on estimating RUL based on SOM and KNNR respectively are proposed. Finally, an ensemble method by combining the output of all aforementioned algorithms is proposed and tested. Principal components analysis and statistical process control were implemented to create T 2 and Q metrics, which were proposed to be used as health indicators reflecting degradation processes and were employed for direct RUL estimation for the first time. It was shown that even when RUL is relatively short due to instantaneous nature of failure mode, it is feasible to perform good RUL estimates using the proposed techniques.